2006
DOI: 10.1002/j.2167-4086.2006.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wish for Revenge

Abstract: The wish for revenge is a ubiquitous response to narcissistic injury, and particularly to the narcissistic injury that accompanies oedipal defeat. Vengeful fantasy serves to represent and manage rage and to restore the disrupted sense of self and internalized imagining audience that have resulted from injury. Clinical and literary examples demonstrate the split within the representation of the self and the imagining other that underlies the wish for revenge, and the way that this split operates differently in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This latter finding can be related to the fact that these former child soldiers were abducted, so recruited against their will, which might lead to higher feelings of revenge afterwards, when being returned back home. A recent study indicated that many child soldiers in northern Uganda perceive themselves as victims [21], or people who because of past experiences of misfortune feel helpless to remedy it [22], Revenge attitudes may arise when a child is hurt and suppresses the rage [23], or may form an attempt to counteract the powerlessness, shame, and isolation possibly associated with the trauma experience [24,25], here in particular the child soldiering experiences. Feelings of revenge may also arise out of perception of unfairness [26] or when the victim is unable to mourn all losses (s)he is confronted with [27].…”
Section: Discussionmentioning
confidence: 99%
“…This latter finding can be related to the fact that these former child soldiers were abducted, so recruited against their will, which might lead to higher feelings of revenge afterwards, when being returned back home. A recent study indicated that many child soldiers in northern Uganda perceive themselves as victims [21], or people who because of past experiences of misfortune feel helpless to remedy it [22], Revenge attitudes may arise when a child is hurt and suppresses the rage [23], or may form an attempt to counteract the powerlessness, shame, and isolation possibly associated with the trauma experience [24,25], here in particular the child soldiering experiences. Feelings of revenge may also arise out of perception of unfairness [26] or when the victim is unable to mourn all losses (s)he is confronted with [27].…”
Section: Discussionmentioning
confidence: 99%
“…Birksted-Breen linked the terror of "nameless dread" (Bion, 1962) to the failure to internalize the time interval of successful containment and the consequent timeless sense that the containing object will never return or respond-a feeling, I think, that Alice had taken in from her father together with his experience of early loss. In addition, patients for whom early difficulties with containment come alive in analysis often experience a split transference to the analyst as a containing mother (Britton, 1998); a negative imago of the containing mother is felt to be impervious to the infant/patient's communications, while a positive imago is felt to be ideally attuned and receptive (LaFarge, 2004(LaFarge, , 2006Zimmer, 2003). Each side of the split containing relationship is elaborated in fantasy, with the sense of negative containment felt as a dissolution of self at the hands of a malignant object, the sense of positive containment endowed with a heightened, sense of synchrony, and a magical capacity to transform experience instantaneously.…”
Section: Time and The Analytic Exchangementioning
confidence: 98%
“…Martens denied. This more superficial kind of forgiveness can be seen as the simple opposite of vengefulness, in which the self is identified with the dark side of the split, a primitive, all-bad superego, implacably bent upon punishment (LaFarge, 2006).…”
Section: Distinctions Between Superficial and Deeper Forms Of Forgivementioning
confidence: 99%